(untitled) (Research, Society and Development, 2022)
Cesarean section increases the probability of maternal mortality and morbidity, such as infections, hemorrhages, pulmonary embolism, complications during anesthesia and others. of childbirth would cease in Brazil; according to literature. A survey of a descriptive research was carried out. In Brazil, cesarean rates have increased considerably in recent years. The Ministry of Health as a strategy has been creating over the years several programs to encourage normal birth, but without reaching desired rates. Cesarean section increases the risk of complications such as: infections, hemorrhages, pulmonary embolism, complications in the anesthetic act and others. Mortality in Brazil is 62 cases per 100,000 births. Since 1990, the rate has been reduced by half, but far from reaching the target set by the UN, a rate of 35 deaths per 100,000 births. The preference for elective delivery is not only due to medical issues, it is also influenced by several psychosocial factors and evidently occurs in developing countries. Several factors that increase the rate of elective cesarean sections are involved: socioeconomic aspects, ethical-legal issues, psychological and cultural characteristics of patients and doctors. Nursing has as an important work tool, communication, which can be used as therapy and put into practice in interpersonal interaction with the patient, facilitating the process and achieving the goals of nursing care.